Civic and Faith Life in College: A Two-Part Investigation of University Students' Political and Spiritual Engagement. Issue 5 (20th October 2019) - Sokol, Bryan W.; Marle, Peter D.
Abstract : This two-part investigation extended research demonstrating the civic impact of college students' spiritual commitments. The initial study served as a large-scale assessment ( n = 768) of political involvement using a new Inventory of Political Activity. The smaller-scale, follow-up study ( n = 129) used two validated measures of spiritual transcendence and meaning-making. Findings suggested that the relationship between faith and politics is complex. Students who identified as "spiritual-but-not-religious" evidenced the highest levels of political involvement.